2011
DOI: 10.1038/labinvest.2010.162
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoceptor blockade in sclerosing cholangitis of Mdr2 knockout mice: antifibrotic effects in a model of nonsinusoidal fibrosis

Abstract: Primary sclerosing cholangitis (PSC) is a cholestatic liver disease with high propensity to develop into cholangiocarcinoma. The hepatobiliary disorder of PSC is due to progressive fibrosis surrounding the intra-and extrahepatic bile ducts. Until now, no effective medical therapy exists. To study the progression of sclerosing cholangitis after inhibition of the sympathetic nervous system by blockade of the b-adrenoceptors, we used the Mdr2 À/À mouse model, which develops periportal fibrosis similar to human PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“…The effect of propranolol in reducing capsular inflammation and thickness, and in modulating collagen deposition on textured implants observed in this experiment is consistent with findings from previous studies of others fibrosis conditions 19 , which showed that the application of nonselective beta-adrenoceptors antagonists inhibits maturation of collagen, reduces the number of vessels, collagen density, number of mast cells, eosinophils and myofibroblasts compared with control 22,23,25 .…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Isupporting
confidence: 91%
“…The effect of propranolol in reducing capsular inflammation and thickness, and in modulating collagen deposition on textured implants observed in this experiment is consistent with findings from previous studies of others fibrosis conditions 19 , which showed that the application of nonselective beta-adrenoceptors antagonists inhibits maturation of collagen, reduces the number of vessels, collagen density, number of mast cells, eosinophils and myofibroblasts compared with control 22,23,25 .…”
Section: Effect Of Propranolol On Capsular Reaction Around Silicone Isupporting
confidence: 91%
“…The literature shows that MDR2 −/− is related to liver regeneration and hepatocarcinogenesis due to a reduction of hepatocyte apoptosis, inflammation, and fibrosis (23)(24)(25)(26). Accordingly, the MDR2 −/− murine model of HCC has important similarities to patients and provides an opportunity to investigate and target the oncogenic processes associated with HCC.…”
Section: Resultsmentioning
confidence: 99%
“…The same group further demonstrated the potential therapeutic mechanism of norUDCA, a side chainmodified UDCA derivative, with Mdr2 Ϫ/Ϫ mice (45,56). More recently, blocking ␤-adrenoceptors by propranolol treatment was found to improve liver architecture, to delay progression of sclerosing cholangitis and to reduce fibrosis in Mdr2 Ϫ/Ϫ mice (176). These findings are now discussed as a potential new therapeutic option to treat human PSC.…”
Section: Animal Models Of Pscmentioning
confidence: 90%